2007
DOI: 10.1007/s00221-007-1230-7
|View full text |Cite
|
Sign up to set email alerts
|

Strategy adoption and locomotor adjustment in obstacle clearance of newly walking toddlers with down syndrome after different treadmill interventions

Abstract: This study investigated how newly walking toddlers with Down syndrome (DS), after different treadmill interventions, adopted clearance strategies and modified anticipatory locomotor adjustment patterns to negotiate an obstacle in their travel path. Thirty infants with DS (about 10 months of age) were recruited and randomly assigned to either a lower-intensity, generalized (LG) treadmill training group, or a higher-intensity, individualized (HI) treadmill training group. Thirteen in each group completed a one-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…People with DS exhibit a number of anatomical and physiological characteristics that differentiate them from people without DS. For example, the brains of individuals with trisomy 21 are smaller and lighter than those of normal individuals [2] and exhibit a lower neuronal density; they also show synaptic irregularities due to the reduction of neurotransmitters [3] and anomalies in myelination processes [4]. Individuals with DS also show alterations in sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…People with DS exhibit a number of anatomical and physiological characteristics that differentiate them from people without DS. For example, the brains of individuals with trisomy 21 are smaller and lighter than those of normal individuals [2] and exhibit a lower neuronal density; they also show synaptic irregularities due to the reduction of neurotransmitters [3] and anomalies in myelination processes [4]. Individuals with DS also show alterations in sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…8,16 The higherintensity, individualized training also has been reported to have a positive impact on adaptive gait and physical activity. 17,18 This study is an extension of the previous treadmill training research involving infants with DS. The intent was to incorporate orthosis use into the lower-intensity treadmill training protocol of Ulrich and colleagues 13 to provide improved biomechanical alignment during stepping practice.…”
mentioning
confidence: 98%
“…Other randomized clinical trials have been applied in infants with Down syndrome and revealed an earlier onset of independent sitting (Ulrich et al 2001) and walking (Ulrich et al 2001;Wu et al 2007;Wu et al 2008), and longer stride length . Furthermore, infants with ID responded better to a high compared to a low-intensity treadmill program, by increasing walking speed, cadence, by decreasing double support duration and by being able to walk over an obstacle at higher rates within a 6-month training period .…”
Section: Balance Improvementmentioning
confidence: 98%
“…More particularly, the selected strategy to cross the obstacle varies from trial to trial (Virji-Babul and Brown 2004) and there is often hesitation prior to obstacle crossing. Furthermore, they need more time to anticipate the obstacle (Smith and Ulrich 2008;Sparrow et al 1998;Wu et al 2008) and therefore, as early as three steps before the obstacle, they may increase the base of stance width and reduce walking speed, cadence, and step length . Regarding the distance of the foot from the obstacle Smith and Ulrich (2008) reported a decrease in people with Down syndrome which makes obstacle crossing more dangerous for tripping.…”
Section: Gaitmentioning
confidence: 98%
See 1 more Smart Citation